2021
DOI: 10.1016/j.ejphar.2020.173688
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling high-affinity binding compounds towards transmembrane protease serine 2 enzyme in treating SARS-CoV-2 infection using molecular modelling and docking studies

Abstract: The coronavirus disease-19 (COVID-19) outbreak that is caused by a highly contagious severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has become a zoonotic pandemic, with approximately 24.5 million positive cases and 8.3 lakhs deaths globally. The lack of effective drugs or vaccine provoked the research for drug candidates that can disrupt the spread and progression of the virus. The identification of drug molecules through experimental studies is time-consuming and expensive, so there is a need fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…For the human TMPRSS2 model, these four ingredients did not clearly bind to the inhibitor-binding site during the docking simulations. However, as the theoretical isoelectric point of TMPRSS2 is 8.58 (M. Pooja et al, 2021), it is presumed that TMPRSS2 is positively charged at the pH of the assay buffer used in this study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For the human TMPRSS2 model, these four ingredients did not clearly bind to the inhibitor-binding site during the docking simulations. However, as the theoretical isoelectric point of TMPRSS2 is 8.58 (M. Pooja et al, 2021), it is presumed that TMPRSS2 is positively charged at the pH of the assay buffer used in this study.…”
Section: Discussionmentioning
confidence: 94%
“…For the human TMPRSS2 model, these four ingredients did not clearly bind to the inhibitor-binding site during the docking simulations. However, as the theoretical isoelectric point of TMPRSS2 is 8.58 (M. Pooja et al, 2021), it is presumed that TMPRSS2 is positively charged at the pH of the assay buffer used in this study. Therefore, anionic surfactants are more likely to bind to TMPRSS2 than cationic or nonionic surfactants, thereby leading to the induction of protein denaturation and inhibitory effects.…”
Section: Discussionmentioning
confidence: 98%
“…Baicalein, a main ingredient of the TCM herbal formula Shuanghuanglian, has demonstrated anti-viral effects through inhibiting M pro activity [ 61 , 62 ]. Additionally, studies have reported that baicalein significantly affects both ACE2 and TMPRSS2 [ 63 , 64 ]. A notable screening study, suggesting the compound as a candidate for the treatment of SARS-CoV-2, reported that baicalein also binds with the SARS-CoV-2 nonstructural protein 14 (NSP14) [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the core of the substrate-binding pocket revealed multiple interactions (such as hydrogen bonding with Leu141/Gly143 and Ser144/His163, π–π interactions with Cys145 and His4, and hydrophobic interactions with Met49 and His41), which effectively blocked SARS-CoV-2 replication via noncovalent incorporation [ 68 ]. The relevant studies [ 70 , 71 , 72 ] provided direct data for a better understanding of the molecular mechanisms of Chinese herbal medicine by studying its active ingredients.…”
Section: Natural Products As Monotherapy For the Treatment Of Sars-cov-2mentioning
confidence: 99%